CLINICAL AND GENETIC PARALLELS ALONG CELIAC DISEASE AMONG TOMSK CHILDREN - E.I. Kondrat'eva; V.P. Puzyrev; L.P. Nazarenko; A.A. Rudko; G.N. Yankina; E.V. Loshkova (Union of pediatricians of Russia, 2007)
The article is devoted to the analysis of the genetic predisposition to celiac disease. The authors studied the associations of the HLA genes and modifier genes of the immune response (interleukine 1, inter leukine 1 receptor antagonist, inter leukine 4, α-subunits of interleukine 4 receptor, receptor to D vitamin) along with predisposition to the disease, as well as the variants of its run and accompanied autoimmune diseases (autoimmune thyroiditis, insular diabetes type 1).Key words: celiac disease, genetic predisposition, genetic analysis.